HUBUNGAN KEBIASAAN KONSUMSI JUNK FOOD, AKTIVITAS FISIK, SOSIAL EKONOMI, DAN PENGETAHUAN GIZI TERHADAP STATUS GIZI SISWA SMAN 10 KOTA TANGERANG - Farah Febrina Hapsari (2022)
Nutritional problems in adolescents are increasing from year to year, especially obesity. Obesity is often impacted by junk food consumption, physical activity, socioeconomic status, and nutritional knowledge. Easy access and cheap types of junk food make teenagers like to consume this type of food. In addition, the COVID-19 pandemic has reduced teenagers' physical activity to sitting, playing on mobile phones, and lying down more often. This study aimed to determine the relationship between junk food consumption habits, physical activity, socioeconomic status, and knowledge of the nutritional status of SMAN 10 Tangerang students. This study used a cross-sectional research design by using the chi-square test. Respondents in this study were students of SMAN 10 Tangerang. As many as 56 respondents took using the cluster random sampling technique. The results showed no relationship between junk food consumption habits, socioeconomic, and nutritional knowledge on the nutritional status of SMAN 10 Tangerang students (P > 0.05). However, there was a relationship between physical activity and the nutritional status of SMAN 10 Tangerang City students (P < 0.05).